Reading the philosophy: Dana Freibach-Heigefetz on generosity-ethics in “The Idiot” by Fyodor Dostoevsky - Górecki, Przemysław (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
Reading the philosophy: Dana Freibach-Heigefetz on generosity-ethics in “The Idiot” by Fyodor Dostoevsky